Does screencast teaching software application needs narration for effective learning? - Mohamad Ali Ahmad Zamzuri, Samsudin Khairulanuar, Hassan Mohamad, Sidek Salman Firdaus, (N/A, 2011)
Does screencast teaching software application needs narration for effective learning? by Mohamad Ali Ahmad Zamzuri, Samsudin Khairulanuar, Hassan Mohamad, Sidek Salman Firdaus,